Ayurvedic Management Of Ardita With Special Reference To Bell’s Pals - A Case Report - Kumar, Ravindra; Kumari, Sujata; Anand; Gupta, Arun (International Research Journal of Ayurveda & Yoga, 2021)
Ardita (Bell’s pals) is considered as one among the eighty Vataj Nanatmajaj Vyadhis (diseases caused due to a single dosha) in Ayurveda. It is correlated with bell’s palsy in modern aspect, which is an acute, apparently isolated, lower motor neuron facial palsy for which there is no specific aetiology. It is characterized by sudden onset of paralysis or weakness of the muscles of one side of face controlled by the facial nerve. The present study was conducted with an objective to find out the effective Ayurvedic management in bell’s palsy. A 45 years old female patient who was suffering from complaints of deviated face on left side, unable to chew from right side, improper blinking of right eye and slurred speech for 20 days. She was clinically diagnosed as bell’s palsy and managed through Panchkarama & palliative treatment for 14 days. The patient showed significant improvement in sign and symptoms.